Interaksi Good Corporate Governance, Corporate Social Responsibility, Intellectual Capital Dan Pengaruhnya Terhadap Kinerja Keuangan Perusahaan: Interaction of Good Corporate Governance, Corporate Social Responsibility, Intellectual Capital and Their Influence on Company Financial Performance - Rosafitri, Citra (Universitas Muhammadiyah Sidoarjo, 2017)
This study aims to determine effect of Good corporate governance, corporate social respinsibility dan intellectual capitalon the financial performance proxied Return on Asset and Return on Equity of companies listed on the Indonesian Stock Exchange. This research method used in this study is a quantitative method to test the assumption of calssical analysis techniques and double linear regresion testing. A sample size of 64 is comprised of 16 companies that meet the criteria specified through purposive sampling. The result of this studi indicate that Good corporate governance consist of institusional ownership, managerial ownership and independent director has no effect on financial performance proxied by Return on Asset and Return on Equity. Corporate social responsibility has effect the Return on Asset and Return on Equity. An than the Intellectual capital consist of VA has effect the Return on asset, and VACA,VAHU, STVA has no effect of Return on Asset, the second proxcied financial performance of Intellectual capital has no effect to Return on Equity. And as well as Good Corporate governance, Corporae Social Responsibility and intellectual capital simultaneously do effect the Financial performace proxied by Return on Asset an Return on Equity.